(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This descriptive study examines how adult EFL learners in Uzbekistan perceive AI-based feedback tools like ChatGPT, Grammarly, and Quillbot in improving writing skills. Six participants( ages 22-33) were purposely sampled and interviewed using semi-structured questions. Data were analysed using line-by-line coding, open codes, axial categories, and emerging themes. Key findings reveal that AI tools foster confidence but may enhance dependency, cause confusion when feedback conflicts teacher guidance, and support conditional autonomy under scaffolding. The study highlights the need for AI literacy training and blended feedback approaches in TESOL; recommendations for teachers, students, and policymakers.